Maternal death trends in Bantul District, Indonesia, over a decade (2015-2024) - Dhiya An, Alfun; Maulidya, Asri Nur; Utari, Kinanti Wilujeng Hayuning (Universitas Airlangga, 2026)
HIGHLIGHTS This study reveals a shifting pattern of maternal death causes over the decade, with Indirect Obstetric Death (IOD) increasing significantly in the last five years, replacing tuberculosis with cardiac diseases as the leading cause of IOD. Postpartum remains the most critical period, accounting for 68.1% of maternal deaths, suggesting that postpartum care is an under-prioritized area that needs urgent health system attention. Health system strategies must move beyond ANC coverage and focus on continuity of care, maternal health literacy, and postpartum surveillance. ABSTRACT Objective: This study aimed to examine trends and shifting patterns of maternal deaths in Bantul District over ten years (2015–2024) to support the development of more targeted and responsive maternal health strategies. Materials and Methods: A retrospective cross-sectional study was conducted using secondary data from the Bantul District Health Office. Maternal death was defined according to the WHO criteria as the death of a woman during pregnancy or within 42 days of termination, irrespective of the pregnancy’s duration or location, excluding accidental or incidental causes. Data sources included official maternal mortality audit reports compiled from medical records and community-based investigations. All eligible cases with complete cause-of-death information were included through total sampling. Data were then grouped into two periods (2015–2019 and 2020–2024) to reflect contextual changes such as the COVID-19 pandemic and evolving maternal healthcare policies. Descriptive statistics, chi-square, and odds ratios (OR) were calculated, with a p-value < 0.05 considered significant. Results: A total of 144 maternal deaths were analyzed: 52.1% were Direct Obstetric Death (DOD), and 68.1% occurred during the postpartum period. Hemorrhage and hypertensive disorders of pregnancy were consistently dominant causes. In the late period, cardiac diseases emerged as a leading indirect cause of obstetric death. Although differences were not statistically significant, higher odds of DOD were observed among women with fewer antenatal care (ANC) visits and lower socioeconomic status during 2020–2024. Conclusion: The findings emphasize the urgent need to shift from access-focused to quality-focused maternal care through early detection of comorbidities, improved postpartum surveillance, and better integration between levels of obstetric care.